2010
DOI: 10.1590/s1519-566x2010000400028
|View full text |Cite
|
Sign up to set email alerts
|

Sazonalidade e uso de ambientes por espécies de Tabanidae (Diptera) na Amazônia Central, Brasil

Abstract: -Adults of Tabanidae may become serious pests wherever they occur due to their attack to humans and others animals. Tabanids were captured near ground, water surface and at 25 m high on primary forests and forest gaps of anthropogenic origin, to understand their abundance, seasonality, diversity and similarity on such environments. Collections were carried out in the Base II of the War Instruction Center in the Jungle (CIGS) located at 54 km from Manaus municipality, Amazonas state. Two Malaise fl ight interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In tropical areas of Brazil, there is a well‐defined rainy and dry seasonality. The highest occurrence of tabanids is likely to occur in central Amazonia, eastern Amazonia, and Pantanal, and they are most abundant between the months from July to December, which matches the hot and dry periods (Gorayeb , Barros and Foil, , Silva et al Barros , Oliveira et al Ferreira‐Keppler et al The pattern is similar to that found in Pampa, where the richness and abundance of horse flies were higher between September and February, when temperatures are higher and the RH is lower than during the rest of the year. Even in Europe, the number of horse fly species of begins to increase in in the second half of May (spring in the northern hemisphere) and decreases in the middle of September (late summer) (Chvala et al , Krčmar , , Hackenberger et al Altunsoy and Kiliç , Mikuška et al Baldacchino et al Herczeg et al ).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In tropical areas of Brazil, there is a well‐defined rainy and dry seasonality. The highest occurrence of tabanids is likely to occur in central Amazonia, eastern Amazonia, and Pantanal, and they are most abundant between the months from July to December, which matches the hot and dry periods (Gorayeb , Barros and Foil, , Silva et al Barros , Oliveira et al Ferreira‐Keppler et al The pattern is similar to that found in Pampa, where the richness and abundance of horse flies were higher between September and February, when temperatures are higher and the RH is lower than during the rest of the year. Even in Europe, the number of horse fly species of begins to increase in in the second half of May (spring in the northern hemisphere) and decreases in the middle of September (late summer) (Chvala et al , Krčmar , , Hackenberger et al Altunsoy and Kiliç , Mikuška et al Baldacchino et al Herczeg et al ).…”
Section: Discussionsupporting
confidence: 66%
“…The species richness in the localities of the Pampa biome is lower than that found in the Pantanal biome (Barros and Foil , Barros ), Jau National Park (Henriques and Rafael , Henriques ), which is between the Amazon and Roraima in the western Amazon (Oliveira et al Ferreira‐Keppler et al however, the observed richness is very close to that which was observed in Tocantins in Cerrado biome (Lima et al This can be explained by the latitudinal gradient, productivity, geologic time, size, and type of sampling areas (Rosenzweig ); these variables provide a consistent set of hypotheses to explain the increased diversity of tabanids in the tropics compared to subtropical areas.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations